Surgical Management of L5-S1 Spondylodiscitis on Previously Documented Isthmic Spondylolisthesis: Case Report and Review of the Literature - Anthony Lubiato; Guillaume Baucher; Mikael Meyer; Stéphane Fuentes (Case Reports in Surgery)
Background. Although lumbar isthmic spondylolisthesis is frequent in the Caucasian population, its association with spondylodiscitis is extremely rare. Case Description. The authors reported the case of a 44-year-old patient affected by pyogenic spondylodiscitis on previously documented isthmic spondylolisthesis at the L5-S1 level. The patient was surgically treated by circumferential arthrodesis combining anterior lumbar interbody fusion (ALIF), followed by L4-S1 percutaneous osteosynthesis using the same anesthesia. Appropriate antibiotherapy to methicillin-susceptible Staphylococcus aureus, found on the intraoperative samplings, was then delivered for 3 months, allowing satisfactory evolution on the clinical, biological, and radiological levels. Discussion. This is the first case report of spondylodiscitis affecting an isthmic spondylolisthesis surgically treated by circumferential arthrodesis. In addition to providing large samplings for analysis, it confirms the observed evolution over the past 30 years in modern care history of spondylodiscitis, increasingly including surgical treatment with spinal instrumentation, thus avoiding the need of an external immobilization. Care must nonetheless be exercised in performing the ALIF because of the inflammatory tissue increasing the risk of vascular injury. Conclusion. Spondylodiscitis occurring on an L5-S1 isthmic spondylolisthesis can be safely managed by circumferential arthrodesis combining ALIF then percutaneous osteosynthesis in the same anesthesia, obviously followed by appropriate antibiotherapy.